(untitled) (Research, Society and Development, 2021)
This article is the result of the interest in analyzing how public security in the State of Rio de Janeiro is thought of from the implementation of Pacifying Police Units (UPPs) in 2008, stating a new way of police intervention in popular communities. It aims at analyzing the impact of UPPs in the slums and favelas, marked by the raise of punishing power and the acceptance from the society of the implementation of authoritarian policies, historically stated by the advance of military power over public security in popular areas. From the advance of readings and development analysis of this “new proposal” of public security we can notice that the UPPs are characterized by the military domination of poor communities and favelas as well as the disciplining of their occupants. Moreover, it aims at understanding the phenomenon of violence in such areas and the apparent need of an external agent to monitor and restrain the actions of their inhabitants. It was taken the following methodological instruments: brainstorming and reading of the theme, articles from eminent popular specialized newspapers and magazines.